2016
DOI: 10.1590/1519-6984.21014
|View full text |Cite
|
Sign up to set email alerts
|

Can microcystins affect zooplankton structure community in tropical eutrophic reservoirs?

Abstract: The aim of our study was to assess whether cyanotoxins (microcystins) can affect the composition of the zooplankton community, leading to domination of microzooplankton forms (protozoans and rotifers). Temporal variations in concentrations of microcystins and zooplankton biomass were analyzed in three eutrophic reservoirs in the semi-arid northeast region of Brazil. The concentration of microcystins in water proved to be correlated with the cyanobacterial biovolume, indicating the contributions from colonial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Cyanophytes can be too large for many gape-limited grazers to consume, either because they form mucilaginous colonies or long filaments (Haney, 1987). The production of cyanotoxins can also be detrimental to grazers, though the magnitude of these effects are debated (Rohrlack et al, 2001;Paes et al, 2016). Conversely, cryptophytes are highly nutritious and are an important component of aquatic food webs (Stemberger and Gilbert, 1985;Sarnelle, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanophytes can be too large for many gape-limited grazers to consume, either because they form mucilaginous colonies or long filaments (Haney, 1987). The production of cyanotoxins can also be detrimental to grazers, though the magnitude of these effects are debated (Rohrlack et al, 2001;Paes et al, 2016). Conversely, cryptophytes are highly nutritious and are an important component of aquatic food webs (Stemberger and Gilbert, 1985;Sarnelle, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature alone may only partly determine bloom formation and it is accepted that a combination of factors are responsible for a bloom to develop: increasing temperatures, decreasing nutrients and increased water column stability (40); temperature has the most pronounced effect on toxicity; the highest toxicity was found at 20°C, but reduced at temperatures in excess of 28°C. According to Paes and his colleagues (41), in all studied reservoirs that experienced toxic blooms water transparency was reduced. P. rubescens abundance appears to be strongly influenced by water transparency, at least in prealpine lakes (42).…”
Section: Abiotic Factorsmentioning
confidence: 97%
“…Even if the cyanobacteria strain is nontoxic or toxic, at least in the case of B. calyciflorus , this type of diet suppresses the population growth; effects were less severe than that produced by toxic M. aeruginosa (73). Is was observed that in eutrophic systems higher abundance of rotifers is often observed with higher abundance of cyanobacteria, which indicates that not all cyanobacteria inhibit rotifer growth (41,74). Additionally, rotifers are affected by three selected forms (unicellular, filamentous, and colonial) of cyanobacteria (73).…”
Section: Rotifersmentioning
confidence: 99%
See 1 more Smart Citation
“…В данном месяце в нижней части водоёма перепад температуры в этом слое приводил к заметному снижению количественных показателей зоопланктона на горизонтах ниже 10 м. Ещё одним фактором, обуславливающим более низкую биомассу зоопланктона поверхностного слоя по сравнению с таковой на глубине 10 м, может быть цветение синезелёных водорослей, токсины которых, накапливаясь, оказывают аллелопатическое угнетающее воздействие на зоопланктон [16,20]. Несмотря на способность доминантных видов зоопланктона питаться как синезелёными водорослями, так и микроорганизмами, размножающимися в условиях детритной пищевой цепи, а также несмотря на резистентность к токсинам синезелёных водорослей [26], слишком высокая концентрация последних в условиях водохранилища летом [28] [24,29]. Преобладание в сообществе зоопланктона мелких видов и молоди веслоногих ракообразных, которые интенсивно развивались и концентрировались в поверхностном слое, приводило к огромной разнице, прежде всего по численности, между поверхностным слоем 0 м (170 тыс.…”
Section: рис 1 участки отбора проб зоопланктона в запорожском водохunclassified